(x^2-2x+3)(x^2-2x+4)=6 решить сам затрудняюсь между закрытием и открытием скобки умножение заранее

даsha3 даsha3    3   16.09.2019 01:20    0

Ответы
Sasha1230981 Sasha1230981  07.10.2020 18:58
(x^2-2x+3)(x^2-2x+4)=6

Меняем
x^2-2x=t \\ \\ (t+3)(t+4)=6 \\ t^2+7t+6=0 \\ t_1+t_2=-7 \cup t_1t_2=6 \\ t_1=-1 \cup t_2=-6

Меняем назад
1) \\ x^2-2x=1 \\ x^2-2x-1=0 \\ (x-1)^2=0 \\ x=1 \\ \\ 2) \\ x^2-2x=-6 \\ x^2-2x+6=0 \\ \frac{D}{4}=1-6=-5\ \textless \ 0
нет решений

ответ: 1
ПОКАЗАТЬ ОТВЕТЫ
zuldzbeysengaz zuldzbeysengaz  07.10.2020 18:58
(x^2-2x+3)(x^2-2x+4)=6 
x^4-2x^3+4x^2-2x^3+4x^2-8x+3x^2-6x+12=6
x^4-4x^3+11x^2-8x-6x+12=6
x^4-4x^3+11x^2-8x-6x+12-6=0
x^4-x^3-3x^3+3x^3+3x^2+8x^2-8x-6x+6=0
x^3*(x-1)-3x^2*(x-1)+8x*(x-1)-6(x-1)
(x-1)*(x^3-3x^2+8x-6)=0
(x-1)*(x^3-x^2-2x^2+2x+6x-6)=0
(x-1)*(x^2*(x-1)-2x*(x-1)+6x-6)=0
(x-1)*(x-1)*(x^2-2x+6)=0
(x-1)^2*(x^2-2x+6)=0
(x-1)^2=0
x^2-2x+6=0(нет решения)
ответ x=1
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра